Proximal neuropathic lesions in distal symmetric diabetic polyneuropathy: findings of high-resolution magnetic resonance neurography - Pham, Mirko; Oikonomou, Dimitrios; Bäumer, Philipp; Bierhaus, Angelika; Heiland, Sabine; Humpert, Per Magnus; Nawroth, Peter Paul; Bendszus, Martin (Diabetes care, 2011)
OBJECTIVE: This study investigated high-resolution magnetic resonance neurography (MRN) in distal symmetric diabetic polyneuropathy (dPNP). - RESEARCH DESIGN AND METHODS: MRN comprised high-resolution transaxial imaging of peripheral nerves of the lower limbs in 20 patients with type 2 diabetes (10 with dPNP, type 2/dPNP[+], and 10 without dPNP, type 2/dPNP[-]), seven patients with type 1 diabetes (two with dPNP, type 1/dPNP[+], five without dPNP, type 1/dPNP[-]), and 10 nondiabetic control subjects. Intraneural T2 lesions, as the main diagnostic criterion of MRN, were detected visually by two independent observers and quantitatively by analysis of T2 contrast ratios. - RESULTS: Multifocal fascicular, symmetric intraneural T2 lesions occurred in the proximal trunks of sciatic nerves in four patients (three with type 2/dPNP[+] and one with type 1/dPNP[+]) but not in control subjects (type 2/dPNP[-], type 1/dPNP[-], nondiabetic control subjects), which was confirmed by quantitative analysis. Clinical severity was higher in patients with T2 lesions (neuropathy deficit score: 10 vs. 7.8; P = 0.05). - CONCLUSIONS: For the first time, proximal neuropathic lesions of dPNP are reported in vivo. This supports that accumulation of proximal, multifocal fascicular injury may be important in disease progression.